((1-2x)/(3-x))=((x-2)/(3x-1))

Simple and best practice solution for ((1-2x)/(3-x))=((x-2)/(3x-1)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((1-2x)/(3-x))=((x-2)/(3x-1)) equation:


D( x )

3*x-1 = 0

3-x = 0

3*x-1 = 0

3*x-1 = 0

3*x-1 = 0 // + 1

3*x = 1 // : 3

x = 1/3

3-x = 0

3-x = 0

3-x = 0 // - 3

-x = -3 // * -1

x = 3

x in (-oo:1/3) U (1/3:3) U (3:+oo)

(1-(2*x))/(3-x) = (x-2)/(3*x-1) // - (x-2)/(3*x-1)

(1-(2*x))/(3-x)-((x-2)/(3*x-1)) = 0

(1-2*x)/(3-x)-((x-2)/(3*x-1)) = 0

(1-2*x)/(3-x)+(-1*(x-2))/(3*x-1) = 0

((1-2*x)*(3*x-1))/((3-x)*(3*x-1))+(-1*(x-2)*(3-x))/((3-x)*(3*x-1)) = 0

(1-2*x)*(3*x-1)-1*(x-2)*(3-x) = 0

5-5*x^2 = 0

(5-5*x^2)/((3-x)*(3*x-1)) = 0

(5-5*x^2)/((3-x)*(3*x-1)) = 0 // * (3-x)*(3*x-1)

5-5*x^2 = 0

-5*x^2 = -5 // : -5

x^2 = 1

x^2 = 1 // ^ 1/2

abs(x) = 1

x = 1 or x = -1

x in { 1, -1 }

See similar equations:

| (5p^3-6p^3+7p-4)-(-8p^2-6p+3+p^3)= | | 14x+2+10x+50=180 | | -21=46+19(-6b) | | (4x+2x)(3x+2x)=480 | | 16x^2+4(x^4-4x^2-4x^2+16)-64=0 | | 4x+2x(3x+2x)=480 | | 69=8c-3 | | 6e-1=11 | | -3t^2-14t+4=0 | | x^2*14x+40=0 | | 8x^2+25x-200=0 | | 20x=192 | | 4x^2+25-200=0 | | ((2x-1)/(x+2))+((x+2)/(2x-1))=(10/3) | | 8x^2-7x=4x-14x^2 | | 0.06/0.02 | | (3x+8)=(9x-4) | | 6x+105=14x-7 | | 119-4x=41x+19 | | 8y+1000/Y=0 | | 2y^2-50y+308=0 | | 135+x=90 | | 8y+1000/Y | | 135+x=180 | | 4/5-2/4 | | -45=-6f(-3f-4) | | -2x+5y+7=0 | | x+40+5x+14+90=180 | | 6/7-2/5 | | 7x+2=13x-3 | | y^2+25y+154=0 | | 4/6-2/9 |

Equations solver categories